(untitled) - Gile, Daniel (Philadelphia, 1995)
It provides readers with the conceptual bases required to understand both the principles and recurrent issues and difficulties in professional translation and interpreting, guiding them along from an introduction to fundamental communication issues in translation to a discussion of the usefulness of research about Translation, through discussions of loyalty and fidelity issues, translation and interpreting strategies and tactics and underlying norms, ad hoc knowledge acquisition, sources of errors in translation, T&I cognition and language availability. It takes on board recent developments as reflected in the literature and spells out and discusses links between practices and concepts in T&I and concepts and theories from cognitive psychology and psycholinguistics.
Keywords: Biên dịch và phiên dịch.,Translating and interpreting